A NEW PERSPECTIVE ON THE AYTYSH BETWEEN ARSTANBEK BUILASHULY AND SUINBAI ARUNULY - Buldybai Anarbai Sagyuly (Vestnik Issyk-Kulʹskogo universiteta, 2025)
This article examines new perspectives on the poetic duel (aytysh) between the Kyrgyz poet-improviser Arstanbek Builashuly and the Kazakh poet-improviser Suinbai Arunuly. The research highlights the significance of talent, the poets’ relentless pursuit of creativity, and their ability to reflect the role and authority of power within society. It also analyzes the poets’ collected works, including folk-preserved pieces and published anthologies. Moreover, the influence of contemporary rulers, such as the Kyrgyz khans Ormon and Jantai and the Kazakh leader Tezek, on the poets’ creative output is examined. Additionally, the research provides an overview of studies conducted by Kyrgyz and Kazakh scholars on the poets’ works.